Clinical Characteristics, Maternal and Fetal Outcomes of Pregnant Women with COVID-19 - Lama, Sushma; Gurung, Padma; Pradhan, Binita; Todi, Sushila; Malla, Anagha Pradhan (Journal of Karnali Academy of Health Sciences, 2023)
Background: Pregnant woman are more vulnerable to COVID infection due to physiological changes in the immune andcardiopulmonary system. The aim of the study is to assess the clinical characteristics, maternal and fetal outcomes ofpregnant patients with COVID-19 in Patan hospital.Methods: This was a descriptive cross-sectional study conducted in Patan hospital from 1 August 2020 to 30 July 2021following approval from ethical committee. The study population comprised of all pregnant women with COVID-19diagnosed by reverse transcriptase polymerase chain reaction test. There were total of 171 cases. The data were obtainedfrom medical records and hospital database system. The statistical analysis was done by using SPSS version 16.Results: In Patan hospital, there were a total of 171 patients who were COVID-19 positive by PCR test. There were totaldeliveries of 4,277 during one year period and hence the incidence was 3.99%. There were 101 (59.06%) caesarean sectionand 70 (40.93%) vaginal deliveries among which one was vacuum assisted delivery. There were two peripartumhysterectomies. Majority of the patients were asymptomatic, common symptoms were cough 29 (16.95%), fever 27(15.78%) and shortness of breath 13 (7.6%). Prematurity was the common fetal complication seen in 28 (16.37%) of thecases. Maternal mortality was seen in 7 (4.09%) patients.Conclusions: COVID-19 is associated with increase maternal morbidity and mortality. Symptoms can be from mild formto much more severe course of illness. Proper treatment and timely referral of severe cases to higher center can improveboth maternal and fetal outcomes in COVID-19 in pregnancy.